Research on the Application of Digital Twin Technology in Educational Design and Teaching Management - Wen, Man (Pinnacle Academic Press Proceedings Series, 2026)
With the rapid development of digital technology, the field of education is undergoing profound and continuous transformation. As an emerging digital technology, digital twin technology has demonstrated significant potential for application in multiple domains, yet its systematic use in education remains at an exploratory stage. This paper focuses on the application of digital twin technology in educational design and teaching management. First, it clarifies the connotations, operating principles, and core elements of digital twins, drawing on application experience in engineering, manufacturing, and smart cities to construct a conceptual framework suitable for educational contexts. It then analyzes the current status and existing problems of educational design and teaching management, including limited personalization, fragmented resource allocation, and insufficient real-time monitoring of teaching quality. On this basis, the study explores innovative applications of digital twins in curriculum and instructional design, such as virtual replicas of learning environments, dynamic learner modeling, and scenario-based simulation to support personalized learning and adaptive teaching. Furthermore, it discusses how digital twins can optimize resource management, support data-driven decision-making, and enhance quality monitoring and evaluation in teaching management through continuous data collection and feedback. Finally, the paper outlines key implementation paths, including technical architecture, data governance, and organizational support, and summarizes the main conclusions, providing theoretical reference and practical guidance for the digital transformation of education.